Challenges and perspectives for pharmacotherapeutic monitoring in patients with chronic non-communicable diseases in the SUS: a literature review (REMUNOM, 2025)
The article aims to identify the challenges and prospects for pharmacists' role in managing non-communicable diseases (NCDs) in Brazil, based on a literature review. The central research question explores the potential expansion of pharmacists' participation in the pharmacotherapy of NCD patients, considering the impact of this professional on public health. The results indicate that pharmacists contribute significantly to treatment quality, patient adherence, and reducing healthcare costs. However, to ensure broader access to pharmaceutical care, a reassessment of public policies is essential, emphasizing the integration of pharmacists within health teams in an interprofessional and collaborative manner. This more inclusive model has the potential to benefit both patients and the sustainability of the healthcare system, promoting more efficient and accessible care.